Os gêneros retóricos e seu caráter poético-argumentativo em Prosopopéia, de Bento Teixeira. - Tofoli, Barbara Faria (2021)
In this dissertation, based on the analysis of epideictic, deliberative and judicial excerpts, we evidence the rhetorical ply of Prosopopéia, by Bento Teixeira, an epilium written in the 16th century in Portuguese America and published in 1601, together with an account of a shipwreck. The work was for a long time considered only as a literary manifestation, and not as literature itself, being depreciated by Brazilian critics, due to its supposed lack of quality and the imitation of the Camonian epic poetry. On the contrary, our reading of the poem is carried out through the reconstruction of the specifics of the historical moment in which it was written, starting from previous studies from researchers as João Adolfo Hansen, Alcir Pécora, Adma Muhana, Marcello Moreira, Guilherme Luz, Marcelo Lachat, Cleber Felipe e Jean Chauvin, in which rhetorical categories of colonial literate practices are evident. The epideictic, deliberative and judicial rhetorical genres were prescribed by rhetors of classical antiquity, when they determined the ways of well speaking in Greco-Roman oratory. Although they have been systematized separately in ancient works, the three genres are related to the establishment of models of behavior, since anything that is praised is also advised and defended. These genres reached the Modern Era, being used in the Luso-Brazilian letters between the 16th and the 18th centuries, in which the reception of Ancient Rhetorical precepts with meanings particular to the context of annexation to the Portuguese Empire. Based on these assumptions, we initially approach the rhetorical genres, starting from works as the Rhetoric, by Aristotle; the Rhetoric to Herenio, of anonymous authorship; the On the orator, by Cicero; the Institutes of Oratory, by Quintilian; some progymnásmata; and two treatises attributed to Menander Rhetor. After, we focus on the epic poetic genre, starting from the Poetics, by Aristotle; the discourses on the poetic art and the heroic poem, by Torquato Tasso; and the Discurso sobre o poema heroico, by Manuel Pires de Almeida, in addition to classifying the poem as an epilium, comparing it with the poem 64, by Catulo. Then, we present different readings on Prosopopéia and instance the recovery of classical principles in its verses, to then analyze the affiliation of the work to rhetorical genres as an argumentative resource in favor of the Lusitanian expansionist purposes.